2020
DOI: 10.3390/ijerph17155472
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Addiction and Risk-Taking Behavior among Chinese Adolescents: A Moderated Mediation Model

Abstract: Objectives: The mobile phone (MP) is an indispensable digital device in adolescents’ daily lives in the contemporary era, but being addicted to MP can lead to more risk-taking behavior. However, little is known about the mediating and moderating mechanisms underlying this relation. To address the gaps in the literature, the present study examined the idea that MP addiction is associated with reduced self-control, which further associates with increased risk-taking behavior. In addition, this study also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 67 publications
(91 reference statements)
0
19
0
Order By: Relevance
“…Mobile phones can make them avoid contact with others to the greatest extent, and in this way can compensate for the lack of information obtained due to the narrow social network [ 36 , 37 ]. The anonymity of using social software on mobile phones can enable them to escape the negative emotions in real life, and moderate use of mobile phones can regulate negative emotions and obtain a sense of happiness [ 38 , 39 ]. Besides, using the extensive functions of mobile phones for entertainment can make individuals temporarily divert their attention from stress and competition and avoid problems [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile phones can make them avoid contact with others to the greatest extent, and in this way can compensate for the lack of information obtained due to the narrow social network [ 36 , 37 ]. The anonymity of using social software on mobile phones can enable them to escape the negative emotions in real life, and moderate use of mobile phones can regulate negative emotions and obtain a sense of happiness [ 38 , 39 ]. Besides, using the extensive functions of mobile phones for entertainment can make individuals temporarily divert their attention from stress and competition and avoid problems [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Student sex (0 = female , 1 = male ), student age, and mother's and father's education (1 = primary school , 2 = middle school , 3 = undergraduate , 4 = graduate student ) were included as covariates in all the analyses because their significant associations with risk‐taking behavior have been demonstrated in previous studies (Dou, Wang et al, 2020; Figner et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In line with this theory, a growing body of research has demonstrated that adolescents with low levels of self‐control are more prone to substance use (Oliva et al, 2019), alcohol abuse (Palm et al, 2021), and aggression (Neaverson et al, 2020). In contrast, adolescents with high levels of self‐control may show more ability to inhibit impulses and delay gratification, resulting in less risk‐taking behavior (Dou, Lin et al, 2020; Dou, Wang et al, 2020; Gottfredson, 2018; Holmes et al, 2019). Consistent with this view, Farley and Kim‐Spoon's (2017) study suggested that parents with less awareness of adolescents' whereabouts were detrimental to adolescents' development of self‐control, thus increasing the risk of drug abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone addiction was measured using a Chinese version of the MPAI [ 30 , 31 ]. 17 items (e.g., You always feel that there is not enough time to use your smartphone) were rated on a 5-point Likert scale from 1 (never) to 5 (always), with higher scores indicating higher addiction severity.…”
Section: Methodsmentioning
confidence: 99%